SWOT Analysis and Marketing Strategy in Hajj and Umrah Travel Business PT Prima Unggul Global Representative Maros - S, Abdillah Reyhan; Pasigai, Moh. Aris; Salam, Abdul (Jurnal Ekonomi Balance, 2025)
The purpose of this research is to explore the marketing strategy of Hajj and Umrah travel at PT. Prima Unggul Global, Maros Representative, using a SWOT analysis approach. This study is a descriptive research employing a qualitative method. Data were collected through interviews with seven informants, including company leadership, marketing staff, finance staff, tour guides, administrative personnel, Hajj/Umrah guides, and Hajj/Umrah agents. The data collection methods used in this study include observation, interviews, and documentation. Based on the results obtained through SWOT analysis, it can be concluded that PT. Prima Unggul Global, Maros Representative, possesses numerous internal strengths. By leveraging these strengths in conjunction with external opportunities, the company can optimize its marketing strategies to increase the number of pilgrims, ultimately advancing and expanding the business. Furthermore, by addressing both internal weaknesses and external threats, the company can develop anticipatory strategies to mitigate potential declines in the number of pilgrims. This proactive approach ensures that competitive pressures do not hinder the growth and sustainability of the travel business.